The social reproduction of labour and macro theory: A compelling and fruitful conjunction - Setterfield, Mark (PSL Quarterly Review, 2024)
The thesis advanced in this paper is that like class and technical change, gender and the social reproduction of labour routinely shape demand formation and/or the supply side of the economy — and as such, reference to the gendered social reproduction of labour should be more routinely incorporated into macro-theoretic analysis. The argument is developed with reference to two familiar issues in heterodox macrodynamics: reconciliation of the equilibrium and natural rates of growth; and the relationship between distribution and growth. Using an existing feminist macro model as a point of departure, it is shown that proper account of the social reproduction of labour and its gendered character creates important new insights into both the processes by which the equilibrium and natural rates of growth might be equalized, and the underlying character (wage- versus profit-led) of the relationship between distribution and growth.